2022
DOI: 10.3390/nano12071045
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Morphology and Electrical/Magnetic Properties of Ni-Mg Nano-Ferrites from a New Perspective

Abstract: Using the auto combustion flash method, Ni1−x+2Mgx+2Fe2+3O4 (x = 0, 0.2, 0.6, 0.8 and 1) nano-ferrites were synthesized. All samples were thermally treated at 973 K for 3 h. The structural analysis for the synthesized samples was performed using XRD, high-resolution transmission electron microscopy (HRTEM), and FTIR. Scanning electron microscopy (SEM) was undertaken to explore the surface morphology of all the samples. The thermal stability of these samples was investigated using thermogravimetric analysis (TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 54 publications
(55 reference statements)
0
6
1
Order By: Relevance
“…The present work indicated that P21, P16, p53, and TGFβ-1 gene expressions using RT-PCR a good predictor of cancer treatment and inhibition of angiogenesis and was inconsistent with other studies done by other authors [47][48][49][50][51][52][53][54][55]. In the end, the application of photo-and sono-activated phytochemical nanoparticle (nano-curcumin) as in vivo anti-tumor therapy opens up a new way of research in cancer treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…The present work indicated that P21, P16, p53, and TGFβ-1 gene expressions using RT-PCR a good predictor of cancer treatment and inhibition of angiogenesis and was inconsistent with other studies done by other authors [47][48][49][50][51][52][53][54][55]. In the end, the application of photo-and sono-activated phytochemical nanoparticle (nano-curcumin) as in vivo anti-tumor therapy opens up a new way of research in cancer treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…To detail these contributions, it is necessary to use an X-ray diffractometer with an ultrahigh resolution, which is not always available. Nevertheless, in the present work, Formulas (5)- (10) for the relationship between structural parameters that are often used in practice were used. Some examples are the works [76][77][78] and the papers cited herein.…”
Section: Structural Analysismentioning
confidence: 99%
“…Ferrites are essential for many recent technological designs of electrical, magnetic, and microwave devices [5][6][7]. The properties of ferrites are influenced by the method of synthesis, the composition, the microstructure features, and the distribution of cations in the tetrahedral and octahedral sites in the lattice of the ferrite [8][9][10]. The distribution of equilibrium between the spinel structure cations depends on ionic, electronic, and polarizing effects [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 O electrolysis, as a commercially viable technology, possesses significant potential for expansion in the industrial sector. The electrochemical cell employed in H 2 O splitting contains the oxygen evolution reaction (OER) occurring at the negative electrode and the hydrogen evolution reaction (HER) taking place at the positive electrode. Theoretical conditions for the splitting of H 2 O are commonly expressed as 1.23 V. However, electrolytic devices employed in commercial applications often operate at 0.8 eV, which has raised significant concerns. To enhance the pace of the reaction, it is important to devise an ideal electrocatalyst capable of reducing the excessive potential associated with both of the above processes. Until recently, it was commonly held that the most effective catalysts for the electrocatalytic process of the OER were expensive metal such as Ru and Ir oxides, as well as those for the HER being Pt oxides. …”
Section: Introductionmentioning
confidence: 99%